Adolescent-Parent Communication on Sexual and Reproductive Health and its Associated Factors among Higher Secondary School Students of Tokha Municipality, Kathmandu, Nepal - Alisha, Gautam; Krishna, Sharma; Sunita, Dhakal; Sarmila, Dhakal; Anugraha, Chand (Journal of Public Health International, 2022)
Introduction Physical, psychological, and emotional growth are among the changes that define the adolescent stage. As compared to other age groups, adolescents are more vulnerable to sexual and reproductive health issues. Parents can become protective and influencing factors for their children to prevent risky sexual behavior. This study aims to assess adolescent-parent communication on sexual and reproductive health and its associated factors.   Methods A descriptive cross-sectional study was conducted among 212 adolescents aged 15–19 in higher secondary schools of Tokha Municipality. A self-administered structured modified questionnaire to assess the communication used the Weighted Topics Measure of Family Sexual Communication (WTM) tool with a simple random sampling technique of data collection. We performed descriptive statistical analysis and chi-square tests to analyze data and assess the association between variables. Data quality was assured through careful questionnaire design, pretesting, and training.  Results The study found that about 75.9% of adolescents had communicated on SRH topics with their parents. Only 56.1%, 50.1%, 55.2%, and 50.5% of adolescents communicated about choosing a life partner, menstruation, physical and psychological changes during adolescence, and the physical growth and development of reproductive organs, respectively, while topics like using birth controls, when to start having sex, pregnancy, how to handle sexual pressure from a partner, STI and HIV/AIDs, about condoms, and abortion had never communicated by 61.3%, 86.6%, 69.3%, 85.8%, 72.2%, 78.8%, and 82.5% of adolescents, respectively. Adolescent-parent communication on sexual and reproductive health was significantly associated with the level of knowledge regarding sexual and reproductive health (X2 = 5.809, p = 0.01, df = 1). Similarly, there was a significant association with the perceived parenting style (X2 =3.932, p =0.04, df =1), living arrangements (X2 =6.376, p=0.01, df =1), and adolescent-parent communication. Conclusion  It concluded that adolescent-parent communication on SRH issues is not satisfactory. Creating an adolescent-friendly environment at home and conducting awareness programs with the help of the local government of the respective schools would help to increase adolescent-parent communication.
Keywords: Adolescent; Parent; Communication; Sexual and Reproductive Health; Kathmandu